The development Problem Solving Abilities of students in grade 3 by teaching and learning STEM education - Leesa, Panisara; Saeng-ngam, Kanyawadee (Journal for Developing the Social and Community, 2023)
The purpose of this research is to develop problem solving abilities. of students in grade 3 by teaching and learning STEM education with a passing score of 70 percent or more, using an action research process based on Kurt Lewin's concept. The sample group used in this research was Grade 3 students at Ban Tha Muang School. Roi Et Province, the second semester of the academic year 2022, consisted of 15 students. The research instruments were 1) 3 learning management plans 2) problem-solving behavior observation form. The researcher analyzed the data from the problem-solving behavior observation form, analyzed the data by finding percentage, mean, processing, compiling, and summarizing the results as an essay. The results showed that Students have scores to assess their problem-solving abilities. Passing the specified criteria, that is, students have scores to assess their ability to solve problems. Passing the criteria of 70% or more, there are 15 people, representing 100%.